Harvard business review on bringing your whole self to work (Harvard Business School Pub., 2008)
Contents: Overloaded circuits: why smart people underperform; The human moment at work; The making of a corporate athlete; Decisions and desire; Leading by feel; The dangers of feeling like a fake...